Cost optimal project scheduling - Klanšek, Uroš (Organizacija (Kranj), 2008)
This paper presents the cost optimal project scheduling. The optimization was performed by the nonlinear programming approach, NLP The nonlinear total project cost objective function is subjected to the rigorous system of the activity preceden- ce relationship constraints, the activity duration constraints and the project duration constraints. The set of activity precedence relationship constraints was defined to comprise Finish-to-Start, Start-to-Start, Start-to-Finish and Finish-to-Finish precedence relationships between activities. The activity duration constraints determine relationships between minimum, maximum and possible duration of the project activities. The project duration constraints define the maximum feasible project duration. A numerical example is presented at the end of the paper in order to present the applicability of the proposed approach.
Keywords: management; projektno vodenje; planiranje; optimiranje